Bold and newly Independent, or Isolated and Cast Adrift? The Implications of Brexit for Intellectual Property Law and Policy*. (21st February 2017) - Farrand, Benjamin
Abstract: What happens when a breakdown in relations results in mutually possessed objectives becoming harder to achieve? This article explores the consequences of the UK's withdrawal from the EU for intellectual property (IP) law and policy. Compared with other fields such as Economic and Monetary Union and the development of the EU's 'social chapter', the UK has been a supportive and proactive player in internal market integration, particularly pertaining to IP protection. As a result of 'Brexit', the EU may find that the impetus for further harmonization and integration in this field is lost, such as with the EU unitary patent. However, the consequences for the UK are likely to be more severe – a loss of influence, both over laws that govern it and in exporting IP norms internationally, as well as a loss of access to certain protections, agencies and market sectors that are within the UK's economic interests.